2006
DOI: 10.1159/000093065
|View full text |Cite
|
Sign up to set email alerts
|

Renal Angiotensin Receptor Type 1 and 2 Upregulation in Intrauterine Growth Restriction of Newborn Piglets

Abstract: Epidemiological and experimental studies suggest that intrauterine growth restriction (IUGR) is associated with abnormalities in kidney development which is thought to be linked with alterations causing adult cardiovascular diseases. The renin-angiotensin system (RAS) plays an important role in the development of renal vascular and tubular structures, and is known to be altered by experimentally induced IUGR. These experimental models of IGUR have been criticized because they may have a more severe impact on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Previous to this study, there have been a number of studies in other species on the effects of IUGR on the fetal renal RAS (38,41,43). In the case of the IUGR rat, there are reports of downregulation of the renal RAS at birth (41,43), whereas in newborn spontaneously growth-restricted piglets, it has been recently reported that there is upregulation of the renal RAS (38).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous to this study, there have been a number of studies in other species on the effects of IUGR on the fetal renal RAS (38,41,43). In the case of the IUGR rat, there are reports of downregulation of the renal RAS at birth (41,43), whereas in newborn spontaneously growth-restricted piglets, it has been recently reported that there is upregulation of the renal RAS (38).…”
Section: Discussionmentioning
confidence: 82%
“…In the case of the IUGR rat, there are reports of downregulation of the renal RAS at birth (41,43), whereas in newborn spontaneously growth-restricted piglets, it has been recently reported that there is upregulation of the renal RAS (38). The differences in findings between species may relate to the relative developmental maturity of the kidneys at birth; in the rat, the kidneys are still undergoing nephrogenesis at birth, whereas in the piglet, it is complete.…”
Section: Discussionmentioning
confidence: 99%
“…AT2-deficient mice show reduced flow-dependent (endothelium-dependent) vasodilatation [28]. Although there are alternative findings in other organs [29], nutrientrestricted (intrauterine growth retarded) ovine fetuses show a reduction of AT2 in the heart [30]. Finally, it has been suggested that low birth weight babies have a functional impairment of endothelial progenitor cells, which are important in vasculogenesis and repair of endothelial damage, in cord blood [4].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was no increase in renal angiotensin I and angiotensin II levels in 28-day prehypertensive rats whose mothers were fed a 6% protein diet (138). Except for one study where the insult was the result of uteroplacental insufficiency, which used quantitative autoradiography, a method that is only reliable in detecting large changes (51), renal angiotensin II AT 1 receptor mRNA and/or protein abundance was greater in rats whose mothers were fed a low-protein diet compared with controls (122,138) and in small-for-gestational age piglets compared with their larger littermates (121). Despite the variability in results in prenatal programming of the intrarenal and systemic renin-angiotensin levels, which is likely the result of differences in the timing of the insult during gestation and the severity of the adverse event, several studies have demonstrated that treatment of rats that had a prenatal insult with an angiotensin converting enzyme inhibitor or angiotensin receptor blocker resulted in a reduction in blood pressure without a change in blood pressure in the control rats (28,51,75,87,129,130).…”
Section: Mechanism For Hypertension By Prenatal Programmingmentioning
confidence: 99%